Nikolay Ivanovich Khvisiuk - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 75th birthday of a famous scientist, organizer of health protection and higher school, recognized orthopaedic traumatologist and vertebrologist Khvisiuk N.I. - Honoured Worker of Science and Engineering of Ukraine, Doctor of Medical Science, professor of the Department of Traumatology, Vertebrology and Anaesthesiology, Honourary Rector of Kharkiv Medical Academy of Postgraduate Education.